Once Upon a Tim - Gibbs, Stuart, 1969-; Curtis, Stacy (New York : Simon & Schuster Books for Young Readers, 2022)
"With no knightly experience but plenty of pluck and an impressive vocabulary, a twelve-year-old peasant, hoping to improve his station in life, volunteers to help a cowardly prince and his not very powerful wizard rescue a princess from an evil, foul-smelling monster."--
Keywords: Knights and knighthood -- Juvenile fiction; Peasants -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Knights and knighthood -- Fiction; Peasants -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Action and adventure fiction; Humorous fiction